P-212 Impact of post-thaw blastocyst culture time prior to transfer on live birth rate in frozen-thawed embryo transfer cycles: a retrospective observational study. (30th June 2022) - Ciaffaglione, M; Reschini, M; Guarneri, C; Sanzani, E; Cecchele, A; Cucè, V; Posa, A; Balli, M; Mangiarini, A; Pinna, M; Viganò, P; Pisaturo, V; et al.
Abstract: Study question: Does post-thaw blastocyst culture time prior to transfer influence the live birth rate in frozen-thawed embryo transfer cycles? Summary answer: Our study revealed that different culture times of frozen-thawed blastocysts prior to transfer does not influence live birth rate. What is known already: Several studies demonstrated a significantly increased clinical pregnancy rate after a frozen-thawed embryo transfer (FET) compared to a fresh embryo transfer (ET). FET reduces the risk of ovarian hyperstimulation syndrome without facing adverse effects of supraphysiological hormonal levels over endometrial receptivity. However, little is known on the effect of post-thaw embryo culture duration prior to transfer on live birth rate in FET cycles. Recent findings described an improved blastocyst morphological grade after a 20-22h post-thaw culture. Of note, the overnight culture of non-ideal morphology thawed blastocysts prior to transfer resulted in an enhanced live birth rate. Study design, size, duration: We compared the live birth rate of patients undergoing FET after a short blastocyst culture time (2-4h) prior to transfer to that of patients in whom thawed blastocysts were transferred after a long embryo culture time (20-22h). Frozen-thawed transfers of blastocysts vitrified at Day 5 and subsequently thawed were evaluated. Only transfers of single blastocyst were included. Participants/materials, setting, methods: The study was conducted at the Infertility Center – Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico, Milan. We included couples with indications for IVF cycles who underwent frozen-thawed blastocyst transfer procedure on the following natural cycles for freeze-all strategy or to transfer supernumerary embryos from 2014-2021. Data were analyzed using SPSS Statistics software. We evaluated statistically significant differences using various tests including Fisher's test, chi-squared test and Wilcoxon's test. Main results and the role of chance: A total of 2012 frozen-thawed cycles were included in the analysis; in 977 of them, blastocysts were transferred after a 2-4h post-thaw period and in 1035, blastocysts were transferred after a 20-22h post thaw culture period. The age of the women was comparable (35.4 ± 4.2 and 35.3 ± 4.1; p = 0.5, respectively in the short and long culture period). According to statistical analysis, no significant difference in pregnancy outcomes was found between the two groups. Live birth rate was respectively 40% and 42% ( p = 0.2) in the short and long post-thaw blastocyst culture period prior to transfer. Limitations, reasons for caution: Our study was limited by the retrospective nature and was performed in a single fertility center. Moreover, only blastocysts vitrified on day 5 were evaluated and findings might not be generalized to day 6 and 7 blastocysts. Wider implications of the findings: These findings might be useful in the context of the organization of the laboratory workflow. Indeed, the possibility to thaw blastocysts on the day before transfer may represent an advantage in order to avoid an overload of the laboratory procedures during very busy days. Trial registration number: 28_2022